Perancangan Augmented Reality Book Sebagai Media Pembelajaran Monumen Bersejarah Menggunakan Metode Marker Based Tracking - Khansa Tsabita; Nurrizqa Nurrizqa (Jurnal Teknologi Informasi dan Multimedia, 2025)
The significant advancements in information technology today have brought numerous benefits across various fields, particularly in education. In the educational sector, technological advancements can be implemented as learning media. Historical monuments are one of the most interesting topics to teach students; however, the limited availability of access and information regarding historical monuments has become a major obstacle in introducing local and international cultural heritage to students. The information currently available is still general in nature, such as books or online sources, which are less visually appealing and not well-supported by interactive media.In addition, not all schools have the facilities that allow students to directly experience historical sites, either through physical or virtual visits. This research aims to design a historical monument learning media based on augmented reality (AR) using the marker-based tracking method. The research method applied is the Multimedia Development Life Cycle (MDLC) method, with implementation stages that can be carried out non-sequentially. The stages include concept, design, material collecting, assembly, testing, and distribution.The research output is an augmented reality book containing materials about historical monuments, barcodes/QR codes, and AR markers. Validation was conducted through black box testing, which was successfully completed. In addition, the augmented reality book was evaluated by a subject matter expert, obtaining a score of 92 (average 9.2, percentage 92%) and a media expert, obtaining a score of 93 (average 9.3, percentage 93%), both categorized as “very good.” User testing involving 20 eighth-grade students from one Islamic junior high school (MTSs) in Aceh Besar resulted in a score of 891, or 89.1%, also categorized as “very good.” Thus, the augmented reality book was successfully designed, and is feasible and suitable for use as a learning medium to deliver material on historical monuments.